2010
DOI: 10.1128/jvi.00928-10
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Ligands Augment Antigen-Specific CD8 + T Lymphocyte Responses Elicited by a Viral Vaccine Vector

Abstract: Toll-like receptor (TLR) ligands are critical activators of innate immunity and are being developed as vaccine adjuvants. However, their utility in conjunction with viral vector-based vaccines remains unclear. In this study, we evaluated the impact of a variety of TLR ligands on antigen-specific CD8 ؉ T lymphocyte responses elicited by a recombinant adenovirus serotype 26 (rAd26) vector expressing simian immunodeficiency virus Gag in mice. The TLR3 ligand poly(I:C) suppressed Gag-specific cellular immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…The activation of TLRs by their cognate ligands leads to inflammatory cytokine production and up-regulation of costimulatory signals and MHC molecules, thereby linking innate recognition with adaptive T and B cell immune responses, as well as memory responses after immune system encounters any pathogen (32,33). Thus, the emerging concept of utilizing TLR agonists as vaccine adjuvant and strategizing to manipulate TLR signaling in this regard are considered herein.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of TLRs by their cognate ligands leads to inflammatory cytokine production and up-regulation of costimulatory signals and MHC molecules, thereby linking innate recognition with adaptive T and B cell immune responses, as well as memory responses after immune system encounters any pathogen (32,33). Thus, the emerging concept of utilizing TLR agonists as vaccine adjuvant and strategizing to manipulate TLR signaling in this regard are considered herein.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been considerable interest in designing adjuvants for human vaccines that target the TRIF pathway of signaling downstream of TLR4 (10)(11)(12)(13). It is clear that the TRIF signaling pathway can induce DC maturation that is sufficient for induction of adaptive immunity without the overwhelming inflammatory response induced by the MyD88 signaling pathway (14).…”
Section: Map Kinases | Lps | Poly I:c | Mavs | Nf-κb Activationmentioning
confidence: 99%
“…61 In conclusion, we demonstrated that HS has potent effects as vaccine adjuvant when co-immunized with inactivated vaccines in mice. To further explore the underlying mechanism of HS adjuvanticity, the transcriptional expression patterns of DCs exposed to HS was assessed.…”
Section: Discussionmentioning
confidence: 60%